2017
DOI: 10.1098/rspb.2017.1784
|View full text |Cite
|
Sign up to set email alerts
|

The Moran effect and environmental vetoes: phenological synchrony and drought drive seed production in a Mediterranean oak

Abstract: Masting is the highly variable production of synchronized seed crops, and is a common reproductive strategy in plants. Weather has long been recognized as centrally involved in driving seed production in masting plants. However, the theory behind mechanisms connecting weather and seeding variation has only recently been developed, and still lacks empirical evaluation. We used 12-year long seed production data for 255 holm oaks (), as well as airborne pollen and meteorological data, and tested whether masting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 63 publications
3
70
0
2
Order By: Relevance
“…In line with the last hypothesis, several empirical studies have shown that daily airborne pollen amounts strongly depends on weather conditions during pollen release and aerial diffusion for many plant species (Garc ıa-Mozo et al 2012;Grewling et al 2014;Kasprzyk et al 2014;Fuhrmann et al 2016;Sabit et al 2016). Likewise, spring weather are related to fruiting intensity in some masting species (Garc ıa-Mozo et al 2012;Pearse et al 2014;Fern andez-Mart ınez et al 2015;Koenig et al 2015;Bogdziewicz et al 2017a;Caignard et al 2017;Nussbaumer et al 2018), which suggests that unfavourable weather conditions for pollen release, aerial diffusion or synchronised flowering may cause pollen limitation (Koenig et al 2012Bogdziewicz et al 2017b).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In line with the last hypothesis, several empirical studies have shown that daily airborne pollen amounts strongly depends on weather conditions during pollen release and aerial diffusion for many plant species (Garc ıa-Mozo et al 2012;Grewling et al 2014;Kasprzyk et al 2014;Fuhrmann et al 2016;Sabit et al 2016). Likewise, spring weather are related to fruiting intensity in some masting species (Garc ıa-Mozo et al 2012;Pearse et al 2014;Fern andez-Mart ınez et al 2015;Koenig et al 2015;Bogdziewicz et al 2017a;Caignard et al 2017;Nussbaumer et al 2018), which suggests that unfavourable weather conditions for pollen release, aerial diffusion or synchronised flowering may cause pollen limitation (Koenig et al 2012Bogdziewicz et al 2017b).…”
Section: Introductionmentioning
confidence: 77%
“…A first set of hypotheses aimed at explaining masting assumes that plants within populations seed synchronously because they all respond to similar weather cues in the same way, resulting in high interannual variability in flowering and seeding, as well as tight synchrony among individuals (Kelly et al 2000(Kelly et al , 2013. Furthermore, the weather effect on resource acquisition and allocation to reproduction, on pollination or on fecundation success can be viewed as environmental constraints, acting as 'veto' on seeding in extreme cases (Kon et al 2005;Bogdziewicz et al 2017aBogdziewicz et al , 2018. For some masting species, statistically significant relationships have been observed between weather conditions and flowering or fruiting dynamics (Inouye et al 2002;Kelly & Sork 2002;Schauber et al 2002;Kelly et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The strength of phenological synchrony is in turn driven by weather. Such population‐wide pollination outcomes may interact with either resource storage or resource switching to produce mast years when large resource pools coincide with high pollination success (Koenig et al ; Pesendorfer et al ; Bogdziewicz et al ).…”
Section: Hypotheses Predictions and Experimental Testsmentioning
confidence: 99%
“…Yet, we have little idea what has driven this change. Prior studies have predicted that masting intensity will increase, decrease, or remain unchanged in response to climate change (Kelly et al ; Koenig et al ; Monks et al ; Bogdziewicz et al ). This uncertainty may partly arise from the fundamentally different mechanisms that appear to underlie masting in closely related taxa (Table ) (Koenig et al ; Pearse et al ; Bogdziewicz et al ).…”
Section: Introductionmentioning
confidence: 99%
“…This hypersensitivity to weather cues could be explained by synergistic effects boosting fruit production because of favorable weather for photosynthesis and nutrient availability. For instance, acorn production in Mediterranean oaks has been reported to be positively associated to spring rainfall which, a part from drought, ameliorates nutrient limitation by enhancing nitrogen mineralization (Smaill et al, 2011;Fernández-Martínez et al, 2015;Bogdziewicz et al, 2017a). Overall, this phenomenon reflects the high costs of reproduction of some species (Sala et al, 2012).…”
Section: Resultsmentioning
confidence: 98%